Clinical and Genetic Analysis of a Patient With Coexisting 17a-Hydroxylase/17,20-Lyase Deficiency and Moyamoya Disease - Huang, Jiaming; Zhou, Danli; Dong, Nan; Ding, Chenzhao; Liu, Yan; Li, Fangping (Frontiers in Genetics, 2022)
17a-Hydroxylase/17,20-lyase deficiency (17OHD) is caused by pathogenic mutations in CYP17A1, and patients present with hypertension, hypokalemia, and sexual infantilism in females or sex development disorder in males. Moyamoya disease (MMD) is a chronic cerebrovascular disease that frequently results in intracranial ischemia or hemorrhage. In this study, we describe a case of 17OHD and MMD in a 27-year-old phenotypically female (46, XY) patient and discuss the clinical features and characteristics of her genetic defect. Clinical, hormonal, radiological, and genetic analyses were performed. Blood samples were collected from the patient for whole exome sequencing (WES). The results of the WES revealed a homozygous intronic mutation (c.297+2T>C) of CYP17A1, which led to combined 17a-hydroxylase/17,20-lyase deficiency and novel variants from PCNT and CNOT3 that might potentially lead to MMD. To our knowledge, this study is the first one concerning 17OHD accompanied by MMD. Additionally, several cases have previously described patients with 17OHD with histories of cerebral hemorrhage or cerebral ischemia. A correlation in genetic levels between 17OHD and MMD could not be found. For the patient with 17OHD and hypertension, risk of cerebrovascular accident should be considered. Cerebrovascular examination in patients with 17OHD may be beneficial for prevention of life-threatening intracranial vascular disease.